2003
DOI: 10.1079/joh2003179
|View full text |Cite
|
Sign up to set email alerts
|

Porcine cysticercosis in village pigs of North-West Cameroon

Abstract: Abstract:A study was carried out in two villages and one marketplace of the Batibo subdivision in North-West Cameroon to determine the prevalence of porcine cysticercosis. The results showed that 4.44% of 383 pigs were positive at tongue examination whereas ELISA detected circulating antigens in 27.7% of 271 pig sera. A questionnaire survey in 140 pig raising households indicated that 59.3% of them lacked latrines while in 75.7% of the households members defecated directly into pigpens. The seroprevalence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 13 publications
6
27
3
1
Order By: Relevance
“…The seroprevalence of porcine cysticercosis recorded in this study by Ag-ELISA was similar to the 57.4% previously reported for a rural community in Venezuela ), the 56.6% reported for Zambia (Phiri et al 2003) and the 40.6-54.8% reported for South Africa (Krecek et al 2008) but higher than the 9.01% and 37.4% reported, respectively, for Ecuador and Bolivia (Rodríguez-Hidalgo et al 2003;Carrique-Mas et al 2001), the 11.0% and 27.7% reported in West Cameroon (Pouedet et al 2002;Shey-Njila et al 2003) or the 23.3% latterly reported in Zambia by Sikasunge et al 2008. As judged by the enzyme immunotransfer blot technique (EITB), seroprevalence for porcine cysticercosis of 5.2%, 35.0% and 29% (Sarti et al 1997;Rodriguez-Canul et al 1999;Widdowson et al 2000); 43.0%, 42.0-75.0% and 65.0% (Garcia et al 1999Moro et al 2003) and 3.2%, 4.4% and 23.5% (Sakai et al 2001) have been reported for, respectively, Mexico, Peru and Brazil.…”
Section: Discussionsupporting
confidence: 89%
“…The seroprevalence of porcine cysticercosis recorded in this study by Ag-ELISA was similar to the 57.4% previously reported for a rural community in Venezuela ), the 56.6% reported for Zambia (Phiri et al 2003) and the 40.6-54.8% reported for South Africa (Krecek et al 2008) but higher than the 9.01% and 37.4% reported, respectively, for Ecuador and Bolivia (Rodríguez-Hidalgo et al 2003;Carrique-Mas et al 2001), the 11.0% and 27.7% reported in West Cameroon (Pouedet et al 2002;Shey-Njila et al 2003) or the 23.3% latterly reported in Zambia by Sikasunge et al 2008. As judged by the enzyme immunotransfer blot technique (EITB), seroprevalence for porcine cysticercosis of 5.2%, 35.0% and 29% (Sarti et al 1997;Rodriguez-Canul et al 1999;Widdowson et al 2000); 43.0%, 42.0-75.0% and 65.0% (Garcia et al 1999Moro et al 2003) and 3.2%, 4.4% and 23.5% (Sakai et al 2001) have been reported for, respectively, Mexico, Peru and Brazil.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it appears that the population of the area is informed of the disease but the epidemiology remains unknown. This situation was also observed by Shey-Njila et al [18] in Cameroon, but unlike our study, 28.6% of the population knew the relationship between teniasis in humans and cysticercosis.…”
Section: Discussionsupporting
confidence: 71%
“…However, what many of these studies seem to agree upon is the high prevalence of T. solium cysticercosis in porcine farming and pork eating populations. This relationship has been systematically reported in various studies on Cameroon and Africa Assana et al, 2001;Shey-Njila et al, 2003;Nguekam et al, 2003;Thomas et al, 2016;Vondou et al, 2002). Incidentally, epilepsy prevalence is also generally higher in areas associated with high rates of porcine farming.…”
Section: Discussionsupporting
confidence: 61%
“…Surveys across Cameroon have demonstrated the strong relationship between porcine farming and cystercecorsis Assana et al, 2001;Prouedet et al, 2002;Shey-Njila et al, 2003). The intensity of this relationship is determined by local hygiene, sanitation and sociocultural factors like feeding pigs by defecating directly into their pens, weak technical capacity to detect and treat T. solium carriers, inadequate meat inspection and the consumption of poorly cooked pork.…”
Section: Patternmentioning
confidence: 99%